China: The story of a movable feast - United Nations Educational, Scientific; Cultural Organization; Anuliina Savolainen (The UNESCO Courier, 2025)
Five thousand years of Chinese culture of food and drink are on display in the exhibition “A Movable Feast: The Culture of Food and Drink in China” in Hong Kong. Its lead curator, art historian Nicole Chiang, explains how ancient food vessels reveal social practices and rituals that continue to resonate today.